Occurrence, spatial distribution, source apportionment, and risk assessment of antibiotics in Yangtze river surface water - Deling Fan; Yan Zhang; Shuai Sun; Bing Zhang; Mengyuan Liang; Jian Xu; Lei Wang (Emerging Contaminants)
The identification and source tracing of antibiotic contaminants in rivers has become a research hotspot. In this study, surface water samples were collected from 67 locations in the Yangtze River Basin, China. The detection rate, concentration, and distribution characteristics of various antibiotics in these water samples were analyzed. Based on these data, the sources of these antibiotics were traced and correlated with factors such as urban population size, industrial activity, and wastewater treatment efficiency within the sampling area. A total of 57 antibiotics were detected in the Yangtze River, with detection rates of roxithromycin, 1,7-dimethylxanthine (1,7-DTX), and florfenicol (FF) exceeding 80 %. The average total concentration of antibiotics was significantly higher in upstream regions (525.4 ng/L) compared with middle regions (89.5 ng/L) and downstream regions (246.6 ng/L). Furthermore, antibiotic concentrations positively correlated with population density and economic development (R = 0.857, p < 0.05). Based on ecological risk assessment and priority indexes, enoxacin, roxithromycin, sarafloxacin, and clarithromycin (CLR) posed medium risks. This research provides scientific guidance for the periodic monitoring and regulation of antibiotic contaminants in river ecosystems.